A Study of Glycerol and Ester Phase Separation on Ethyl Ester Production from Refined and Crude Palm Oils - Natthrit Roekngam (Prince of Songkla University, 2013)
Thesis (M.Sc. (Biochemistry))--Prince of Songkla University, 2012